Archiv DAI Rom, Italien: Zeichnungen des Instituto di Corrispondenza Archeologica in Rom - Unger, Marina (e-Forschungsberichte des DAI, 2023)
A collection of drawings – the so called Gerhard’scher Apparat – is preserved in the archive of the Rome Department of the DAI. The drawings depicting archaeological items and monuments were either sent by correspondents or commissioned by the secretaries of the Institute e.g. in close cooperation with international art collectors and/or dealers. Now they represent a valuable source for a whole range of research topics, for example the visualisation of archaeological artefacts: the graphical presentation of monuments is an essential part for a discipline studying the material culture of the past and the drawings archive with its variety of examples offers an excellent basis to start from.